Mapping Oklahoma's response to human trafficking: data and partnerships - Mahaffey, Lucy (2020)
Three questions underpin this research. What is the nature of human trafficking in Oklahoma? Who is currently responding to this problem and how? What gaps are there in anti-trafficking response? There is no centralized database and actors turnover with some regularity, making it difficult to form a coherent picture. With surveys and interviews the author attempts to fill this gap. Ultimately, there are next to no resources or data on labor trafficking. While it is imperfect, Oklahoma is beginning to form a picture of adult sex trafficking. Throughout Oklahoma there are two task forces, three main law enforcement agencies, and three victim service providers certified to directly serve sex trafficking victims. Results suggest Oklahomans should work to understand their unique local context, particularly regarding Tribes and jurisdictions. The author concludes with seven areas for future research and key findings and recommendations on ten areas: legislation, data, culture, perceptions, actors/activities, location, measuring, partnerships, good work, and priorities versus moving forward.